Knowledge, Learning and Innovation: Research Insights on Cross-Sector Collaborations - Ratten, Vanessa; Braga, Vitor; Marques, Carla Susana (Contributions to Management Science. New York: Springer Nature, Springer, 2018)
Twelve papers examine knowledge, learning, and innovation in order to enhance competitiveness. Papers also explore perspectives of cross-sector collaboration, intrafirm and interfirm connections, gender, and relational marketing. Papers discuss knowledge, learning, and innovation–research into cross-sector collaboration; entrepreneurial competencies and firm performance in emerging economies–a study of women entrepreneurs in Malaysia; whether online cocreation influences lead users' and opinion leaders' behaviors; knowledge and innovation in Portuguese enterprises; social ties and human capital in family small- and medium-sized entrepreneurial internationalization; perceived social support and social entrepreneurship–gender perspectives from Turkey; entrepreneurship challenges and gender issues in the African informal rural economy; the construction of a professional identity of a female entrepreneur; knowledge creation and relationship marketing in family businesses–a case-study approach; the gender question and family entrepreneurship research; a composite-index approach to detecting reporting quality–the case of female executives in family firms; and influencing factors in customers' intention to revisit resort hotels–the roles of customer experience management and customer value. Ratten is Associate Professor at La Trobe University. Braga is Associate Professor of the Technology and Management at the Polytechnic Institute of Porto. Marques is Assistant Professor and Coordinator of the Innovation, Markets and Organization Research Group in the Centre for Transdisciplinary Development Studies at the University of Tras-os-Montes and Alto Douro. No index.
Pour que la collaboration intersectorielle réussisse, il est nécessaire qu'elles partagent les connaissances et l'innovation par le biais d'un processus d'apprentissage. Ouvrage « fournissant de nouvelles perspectives sur les moyens de stimuler la collaboration intersectorielle ». Présentations de plusieurs méthodes unifiant connaissance, apprentisage et innovation | Exemples : entreprises portugaises, PME familiales, économie sociale informelle africaine, perspective de genre en Turquie etc.
Keywords: Europe; Idéation; dialogue et maillage; Réservé UdeM; Étude de cas